Population pharmacokinetics of oseltamivir in non‐pregnant and pregnant women. (18th August 2015) - Pillai, Venkateswaran C.; Han, Kelong; Beigi, Richard H.; Hankins, Gary D.; Clark, Shannon; Hebert, Mary F.; Easterling, Thomas R.; Zajicek, Anne; Ren, Zhaoxia; Caritis, Steve N.; Venkataramanan, Raman
Abstract: Aims: Physiological changes in pregnancy are expected to alter the pharmacokinetics of various drugs. The objective of this study was to evaluate systematically the pharmacokinetics of oseltamivir (OS), a drug used in the treatment of influenza during pregnancy. Methods: A multicentre steady‐state pharmacokinetic study of OS was performed in 35 non‐pregnant and 29 pregnant women. Plasma concentration–time profiles were analyzed using both non‐compartmental and population pharmacokinetic modelling (pop PK) and simulation approaches. A one compartment population pharmacokinetic model with first order absorption and elimination adequately described the pharmacokinetics of OS. Results: The systemic exposure of oseltamivir carboxylate (OC, active metabolite of OS) was reduced approximately 30 (19–36)% ( P < 0.001) in pregnant women. Pregnancy significantly ( P < 0.001) influenced the clearance (CL/ F ) and volume of distribution ( V / F ) of OC. Both non‐compartmental and population pharmacokinetic approaches documented approximately 45 (23–62)% increase in clearance (CL/ F ) of OC during pregnancy. Conclusion: Based on the decrease in exposure of the active metabolite, the currently recommended doses of OS may need to be increased modestly in pregnant women in order to achieve comparable exposure with that of non‐pregnant women.